Economics and politics of international investment agreements - Henrik Horn; Thomas Tangerås (Research Institute of Industrial Economics (IFN), 2016)
This paper investigates the design and implications of international investment agreements. These are ubiquitous, potent and heavily criticized state-to-state treaties that protect foreign investment against host country policies. We show that optimal agreements cause national but not global underregulation ("regulatory chill"). The incentives to form agreements and their distributional consequences depend on countries' unilateral commitment possibilities and the direction of investment flows. The benefits from agreements between developed countries accrue to foreign investors at the expense of the rest of society, but this is not the case for agreements between developed and developing countries.
Keywords: F21; F23; F53; K33; 330; Foreign direct investment; expropriation; international investment agreements; regulatory chill; Auslandsinvestition; Internationales Investitionsrecht